(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In this article, at the moment when the globalization process is intensifying, through a typological study of the jokes of the American and Uzbek peoples, the comparison of the Uzbek culture with the culture of the oceanic peoples, and the artistic and aesthetic cultural views of the people of the two countries, as well as the values, beliefs and social values of each culture, by studying the themes and structures of the jokes. the concepts of dynamics have been expressed.